The combined effects of vitamin A-deficiency and cigarette smoke on rat tracheal epithelium. - Shields, P. A. (1987)
The effects of 1-14 days cigarette smoke inhalation on the morphology of airway epithelium were compared in normal and vitamin A-deficient rats. Control rats for each diet group received 'sham' exposure of air only. The vitamin A-deficient diet caused highly significant decreases in plasma retinol and liver retinyl palmitate (P less than 0.001). Vitamin A-deficiency alone caused a squamous change without stratification which resulted in a slight but statistically significant decrease (P less than 0.005) in the thickness of tracheal epithelium. In rats fed a diet containing an adequate amount of vitamin A (i.e. 4000 iu/kg), cigarette smoke exposure for 14 consecutive days caused cell hyperplasia and hypertrophy and significant thickening of tracheal epithelium (P less than 0.01) without any squamous change. In vitamin A-deficient rats, cigarette smoke caused an epidermoid metaplasia with epithelial thickening in excess of that seen with cigarette smoke alone: i.e. the thickened epithelium was stratified, keratinized and squamous. The increase in thickness was evident after 7 days and maximal after 14 days of smoke exposure whilst the epidermoid change was most pronounced at 7 days. Whilst no secretory cells were detected in the squamous areas, the number of mucous cells in the intervening mucociliary epithelium was greatly increased. Vitamin A-deficiency may, therefore, augment the metaplastic effects of cigarette smoke by favouring an early, florid epidermoid response.